Literature Review: Gangguan Mental Depresi Pada Wanita - Kurniasari Pratiwi; Dinik Rusinani (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2022)
Depression is a form of mental health condition experienced by many people and oftenoccurs along with anxiety. Depression can be mild and transient, or severe andprolonged. There are people who experience depression only once in their life; somehave experienced it many times. Depression is one of the main causes of suicide(suicide). Based on the data as much as 40% of patients depressed people havesuicidal ideation, and only about 15% are successful in doing so. WHO predicts thatby 2020, depression will be one of the most common mental disorders and majordepression will be the second leading cause of death after heart attacks. Depressionis a mental disorder characterized by a prolonged feeling of sadness and loss ofinterest in activities that are usually done with pleasure. Signs of depression include abad mood such as prolonged sadness, hopelessness, feelings of guilt andmeaninglessness so that all mental processes (thinking, feeling and behaving) can affect motivation to engage in activities in daily life and interpersonal relationships.Another sign of depression is stopping your usual daily activities for at least two weeks.Keywords: Depression, women, literature review